WORKLOAD ANALYSIS FUNGSIONAL DAN MENTAL UNTUK JOB DESIGN - Mardiyanti, Ressy (Esa Unggul University, 2019)
AbstractThis study aims to determine the workload and needs of employees as a basis for the company to run an efficiency program. Based on management's assessment at the beginning of PT. ABC stated that in East Java Bali Nusra (EJBN) total of employees is very high, but the opinion of the head of the region is not true. This study is an applied research specifically evaluation research. The research subjects were taken by cluster sampling technique. The research location is PT. ABC especially the EJBN region with a total of 23 employees, headquartered in Surabaya. From the research, it is known several things, namely the procedures for preparing / reviewing job descriptions, workloads and employee needs for each position. Some functions underload work, such as Marketing Coordinator, Courier, Customer Relation Officer (security), Health Service Admin. Some are in the normal criteria, including the functions of Marketing, Support / admin marketing, Engineer marketing, Finance & Treasury Support, computer support spesialist, General Affair Coordinators, Drivers, Operational Coordinators, Customer Relation Officers (Bali, NTT, NTB, KAI, Janitor, etc.). The function that is in the overload criteria is in the Head of EJBN position, Treasury, Controllers, and Chief Financial Coordinator, Personal Recruiter, and Customer Relations Officer who handles Customer Service in one company. Based on these data, the researcher designed the intervention, namely making job design by means of job enrichment, job enlargement, and rotation. Key Words : job design, job description, workload